The pain and behavior of women during labor and the different positions for childbirth - Nilsen, Evenise; Sabatino, Hugo; Lopes, Maria Helena Baena de Moraes (Revista da Escola de Enfermagem da USP, 2011)
This study evaluated the pain intensity and behavior during labor and delivery, among women who had natural childbirth, without analgesia, in one of the following positions: semi-sitting, lying on the left side, and lithotomy. This is a descriptive, cross-sectional and correlational study. The instruments used were a validated questionnaire that evaluates pain and behavior during labor and childbirth, from the women's perspective, and two pain scales: one analog and one alphanumerical. It was observed that the pain among women who had childbirth in a lithotomy position was significantly smaller compared to those lying on the left side (p=0.003), though women chose the positions. There was an association between pain and behavior. Pain in labor and childbirth were associated among each other, as was the behavior in these two moments. The results point at an association between the position at childbirth and pain, but it was not possible to identify factors to explain this association; therefore, there is a need for longitudinal studies.